Xiao-Xu-Ming decoction prevented hemorrhagic transformation induced by acute hyperglycemia through inhibiting AGE-RAGE-mediated neuroinflammation. (July 2021) - Liu, Nannan; Liu, Chengdi; Yang, Yujiao; Ma, Guodong; Wei, Guangyi; Liu, Shan; Kong, Linglei; Du, Guanhua
Abstract: Stroke is one of the leading causes of death worldwide. Hemorrhagic transformation (HT) is a common serious complication of ischemic stroke (IS) and is related to poor prognosis. Hyperglycemia after stroke is associated with the occurrence of HT and seriously affects the clinical treatment of stroke. Our previous experiments demonstrated that the Xiao-Xu-Ming decoction effective components group (XXMD), which is a Chinese medicine formula reconstituted by active ingredients, has multiple pharmacological effects in the treatment of IS. However, the effects of XXMD on HT after IS remain unclear. Thus, we investigated the preventive effects of XXMD on hyperglycemia-induced HT and further explored the underlying mechanism. Acute hyperglycemia combined with the electrocoagulation cerebral ischemia model was used to establish the HT model. XXMD (37.5, 75, 150 mg/kg/d) was given by gavage for 5 days. Network pharmacology was used to predict potential targets and pathways of XXMD in HT occurrence, and further studies confirmed the related targets. The results showed that hyperglycemia aggravated neurological deficits and blood-brain barrier (BBB) disruption, leading to intracerebral hemorrhage. Pretreatment with XXMD improved neurological function and BBB integrity and inhibited HT occurrence. Network pharmacology revealed that AGE-RAGE-mediated neuroinflammation may be associated with hyperglycemia-induced HT. Further studies confirmed that hyperglycemia activated the AGE-RAGE signaling pathway, increased the expression of HMGB1, TLR4 and p-p65, and induced the release of inflammatory factors and neutrophil infiltration, leading to HT. XXMD could inhibit AGE-RAGE-mediated neuroinflammation. These findings indicated that pretreatment with XXMD alleviated hyperglycemia-induced HT, which may be associated with the inhibition of AGE-RAGE-mediated neuroinflammation. Therefore, XXMD may be a potential therapeutic drug for HT. Graphical Abstract: ga1 Highlights: HT is a common and serious complication after ischemic stroke. Hyperglycemia promotes the occurrence of HT and worsens prognosis of stroke. Pretreatment with XXMD alleviates BBB disruption and the incidence of HT. Pretreatment with XXMD inhibits AGE-RAGE-mediated neuroinflammation.